PENGARUH PERTUMBUHAN PENJUALAN, PROFITABILITAS, DAN KEBIJAKAN DIVIDEN TERHADAP PERUBAHAN LABA - Silviana, Rima; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to examine whether sales growth, profitability, and dividend policy have influence to the changes in profit. The data is the secondary data. The sample collection method has been done by using purposive sampling method. The analysis technique has been done by using multiple linear regressions. The result of this research shows that sales growth and profitability have positive influence to the changes in profit; it means thatthe size of the sales growth of the company influences therate of changes in profit. If the sales growth is high, the changes in profit will be high as well. Profitabilityin this caseshows theability of the company togeneratenet profiton certain sales. If profitability is high, the changes in profit will be high. The dividend policy does not have any positive influence to the changes in profit; it means thatthe amount ofthe dividends which have been paid by the companyto the shareholdersdo notinfluence the changes in profit.Keywords:Sales Growth, Profitability, Dividend Policy, Changes in Profit.